(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
In this paper experimental investigation of major and minor hydraulic losses, ie the friction and resistent coefficients was performed on several characteristic fittings within the pressurized pipe system. For the purpose of calculating these coefficients, relevant formulas have been given for their determination. Within the work on the physical model GUNT HM 150 as a part of the Practicum Hydro-technical laboratory of the Faculty of Civil Engineering in Rijeka, three basic experimental measurements were conducted: calculation for defining minor hydraulic losses on the pipe joint (under an angle of 45° and 90°), hydraulic analysis from the changes of the cross section of the pipe (gradual narrowing and widening of the pipes), and hydraulic analysis from the branching of the pipe legs (branched part of the pipe system). At the end of the paper, conclusions were given based on the conducted experimental tests, as well as guidelines for future additional tests of minor and major hydraulic losses on the given physical model.